Numerical simulation of snow deposition around structural snow fences - K. Litvintsev Yu.; A. Gavrilov A.; A. Dekterev A.; Yu. Zaharinsky N.; A. Minakov A.; S. Filimonov A.; K. Finnikov A.; К. Литвинцев Ю.; А. Гаврилов А.; А. Дектерев А.; Ю. Захаринский Н.; А. Минаков В.; et al. (IGRAS, 2023)
The results of numerical modeling of the influence of geometric characteristics of snow-protecting fences on the intensity of snow deposition at the initial stage of formation, that is, without taking into account the influence of the dynamics of the shape of the snow cover surface, are presented. In the most industrialized and densely populated region on the Arctic Krasnoyarsk Territory - the industrial City of Norilsk, daily snowfall can exceed 50 mm, the snow depth reaches, on the average, 47 cm (the largest is 70 cm), while the wind speed - 25-30 m/s. This promotes formation of snow deposition on roads, in residential areas as well as in industrial sites and infrastructure facilities, which hampers and sometimes completely stops operation of them. As part of the solution of these problems, a software package has been developed aimed at numerical modeling of snow transport processes and implementing the snow protection measures. To simulate the dynamics of the windinduced snow drift, a microscale model of the atmospheric boundary layer was used together with a diffusion-inertial description of the transport of the snow dispersed phase. Analysis of the calculation results shows that the width of the plates, as well as their spatial orientation, have insignificant effect on the snow-holding capacity of fences. The size of the gaps between the rails and the height of the lower gap exerts the greatest influence on the distribution of the intensity of snow deposition, both on the leeward and windward sides of the fence. In general, we can talk about the relationship between the wind speed field formed during the drift around the fence and the distribution of the snow deposition intensity. Thus, a relative decrease in the average wind speed from the leeward side of the fence increases the precipitation intensity. The presented results of numerical modeling do not contradict data of field observations previously obtained by other authors, and, thus, the developed software package allows comparing effectiveness of ...